(untitled) (Jurnal Bina Praja, 2018)
The role of NGOs is important because it is carried out directly by the community in general without any restrictions in terms of both quantity and time, so it is expected that it is difficult for collusion to happen between NGOs and corruptors. However, in practice, the role of NGOs can become elitist and NGOs are not rooted in the community and do not represent the interests of the wider community so that the role of NGOs can be manipulated by officials for personal gains. This study aims to describe the role of NGOs in its function as a social control agent in the eradication of corruption in North Bengkulu Regency. By using a qualitative approach and descriptive type of research, data collection is done through interviews, documentation, and observational studies. The results of this study indicate that there are 3 (three) main roles of NGOs, namely educative, advocative, and investigative roles. The role of non-governmental organizations in building community awareness is only carried out by a small number of NGOs with limited frequency. The role of non-governmental organizations in the form of advocacy on government policies is carried out passively by providing input when requested by local governments such as in meetings or discussions arranged by the government. The role of non-governmental organizations in the form of demonstrations against corruption behavior and practices is still very limited by non-governmental organizations in North Bengkulu. While the role of non-governmental organizations in the form of investigations on corrupt practices has been carried out by almost all non-governmental organizations engaged in the eradication of corruption and the monitoring of the administration of governance in North Bengkulu, but follow-up efforts to encourage an official investigation into the results of the investigation have not been maximized and even some Non-governmental organizations utilize the results of investigations to obtain personal gains.